PENGARUH PENGELOLAAN KELAS TERHADAP MOTIVASI BELAJAR SISWA KELAS VIII DI SMP NEGERI 1 SINGKEP PESISIR - Ilham Andika Putra; Intan Nurfitri; Muhammad Syahwandi (Sekolah Tinggi Ilmu Tarbiyah (STIT) Lingga, 2025)
This study aims to determine the effect of classroommanagement on the learning motivation of eighth-grade students atSMP Negeri 1 Singkep Pesisir. Effective classroom management isexpected to create a conducive learning environment that canenhance students' motivation. The research method used isquantitative, employing the Product Moment correlation formulawith a total of 48 respondents.Data collection techniques werecarried out through questionnaires measuring aspects of classroommanagement and learning motivation. The analysis results indicatea significant positive relationship between classroom managementand student learning motivation, with a correlation coefficient of0.709. The significance value is less than 0.05, indicating acorrelation, while Pearson's correlation ranges from 0.060 to0.799, reflecting a strong relationship between the two variables.Good classroom management practices, such as classroomarrangement, interaction management, and the implementation ofclear rules, can enhance students' learning motivation. Therefore,it is recommended that teachers at SMP Negeri 1 Singkep Pesisirpay more attention to these aspects of classroom management.